Hubungan Status Gizi dan Tingkat Aktvitas Fisik dengan Siklus Menstruasi pada Remaja Perempuan di SMAN 7 Denpasar - Komang Trinia Amanda Riadi; Anak Agung Gede Budhitresna; Putu Austin Widyasari Wijaya (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
As many as 87% of women with menstrual cycle irregularities have a higher risk of experiencing (polycystic ovarian syndrome) due to impaired ovarian function. Irregular menstrual cycles also have a 2.01 times higher risk of developing diabetes mellitus. The prevalence of women who experience irregular menstrual cycles is more common in adolescent girls aged 16-18 years who are overweight and have a sedentary lifestyle. This study aims to determine the relationship between nutritional status and level of physical activity and the menstrual cycle in adolescent girls at SMA Negeri 7 Denpasar. The research subjects were class XI students of SMA Negeri 7 Denpasar who met the inclusion criteria and numbered 74 people. The sampling method uses simple random sampling. The research method is a quantitative method using a cross sectional design. Data regarding nutritional status was collected through measuring body weight and height, while data regarding physical activity and menstrual cycles were collected through filling out questionnaires by respondents. The research data were analyzed using the Pearson Chi Square test and multinomial logistic regression test. From the research results, it was found that the dominant respondents had normal nutritional status (68.9%), carried out moderate levels of physical activity (42.3%) and experienced normal menstrual cycles (60.8%). Based on the bivariate test, it shows that there is a relationship between nutritional status and physical activity level with a value of p = 0.000. Apart from that, there is a relationship between physical activity levels and the menstrual cycle (p= 0.014). The dominant independent variable that plays a role in the menstrual cycle is nutritional status.